213k views
4 votes
5(x-3) = 2(x+3) solve for x

User Lavell
by
5.1k points

2 Answers

6 votes

Answer:

7

Explanation:

5(x - 3) = 2(x + 3) Distribute

5x - 15 = 2x + 6

+ 15 + 15 Switch sides to the liked terms

5x = 2x + 6 + 15

-2x -2x Switch sides to the liked terms

5x - 2x = 6 + 15

3x = 21 Divide

3 3

x = 7

User Carsten Gehling
by
4.9k points
4 votes

Answer:

x = 7

Explanation:

Equation: 5(x-3) = 2(x+3)

Step 1: Simplify the equation.

5 (x − 3) = 2(x + 3)

(5)(x) + (5)(−3) = (2)(x) + (2)(3) Distribute

5x + −15 = 2x + 6

5x − 15 = 2x + 6

Step 2: Subtract 2x.

5x − 15 −2x = 2x + 6 −2x

3x − 15 = 6

Step 3: Add 15.

3x − 15 + 15 = 6 + 15

3x = 21

Step 4: Divide by 3.


(3x)/(3) = (21)/(3)

Step 5: Divide 21 by 3.

The answer is x = 7.

User Thebiffboff
by
4.4k points